Adaptasi Ekonomi Sirkular Terhadap Reduksi Timbulan Sampah di Kapanewon Kabupaten Bantul: Analisis Data Panel dan Spasial - Ainina Ratnadewati; Deana Aulia Juvitasari (Jurnal Riset Daerah, 2024)
The swift advancement of our times continues to present waste as a significant challenge that requires our attention. Countermeasures are carried out with efforts that combine environmental and economic aspects or what is called a circular economy. The purpose of this study is to analyze the relationship between the independent variables, namely GDP, area, population, and circular economy implementation efforts with the dependent variable measured is the amount of daily waste generation. This research adopts a mixed method, which includes a quantitative approach through panel regression and a qualitative approach with mapping using Geo-Map orange data mining. This research was conducted in 17 kapanewon in Bantul Regency. The results showed that the amount of daily waste generation at kapanewon in Bantul Regency was influenced by GDP, population, and TPS3R with a probability value of 0.000 <0.05. The results on each variable are that the GDP variable has an influence of 0.25 on the circular economy, the population has an influence of 1.05. Meanwhile, the TPS3R variable has a coefficient of -1.42, which shows that the role of the Bantul Regency government in reducing the amount of waste generation is quite effective. This shows that the population gives the biggest role in the amount of waste generation in each kapanewon in Bantul Regency